Career preferences and influencing factors among students entering medical school - Muraleedharan, Aparna; Menon, Vikas; Raj, Gladwin Victor (International Journal Of Community Medicine And Public Health, 2019)
Background: Little information is available on the prospective career choices of students entering medical school. So, this study was designed to assess career preferences of fresh medical undergraduates in the Indian setting and evaluate factors influencing their career choices. Methods: A cross-sectional assessment was carried out on 144 freshman year medical students within 2 weeks of joining the course. All participants completed a self-administered study questionnaire. Five specialties – Internal Medicine, Surgery, Psychiatry, Pediatrics, and Gynecology were chosen for comparison. Responses were rated on a 5 point Likert scale. Data was analysed using SPSS version 18.0. Results: Over one third of the undergraduates reported that they have not made any opinion on their specialty yet. The most popular specialties were Internal medicine, General Surgery and Paediatrics. The least popular specialty was Obstetrics & Gynecology. “Ability to help people” and “challenging nature of work” was chosen by most of the respondents as a very important factor while making a choice of specialization while financial reward was not perceived to be that important. Conclusions: Freshman medical students have several criteria in choosing their specialty and they are modifiable. Medical educators and administrators should think about curricular or teaching reforms to further enhance career counseling and medical education curricula which could potentially motivate more students to take up career in fields lesser chosen.